READING LAW AND IMAGINING JUSTICE IN THE WAHKOHTOWIN CLASSROOM - Buhler, Sarah (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2017)
This article analyzes an innovative community-based educational project called the “Wahkohtowin class” in Saskatoon, Saskatchewan.  The class brings together former gang members, Indigenous high-school students and university students from the disciplines of law, English, and Indigenous studies to learn together about law, justice, and injustice. Students in the class read legal texts together and then discuss and critique these texts in the context of the lived experiences of people in the class. Drawing on the experience of the Wahkohtowin project, this article argues that the practice of lawyers and law students reading and interpreting legal texts and talking about justice together with members of marginalized communities is an “access-to-justice innovation.” It is an innovation because it is a model that positions lawyers and law students not as experts but, rather, as co-learners and co-creators of knowledge with people who possess important lived experiences of the impacts of law and the justice system. It resists the notion that the legal system or lawyers possess a monopoly on justice, opening space for lawyers, law students, and community members to imagine justice together. Overall, this article argues that it is important for those within the legal system who are seeking to improve access to justice to engage with, and learn from, members of marginalized communities who have direct experience with the justice system and that the Wahkohtowin class is one example of how this can happen.